2023
DOI: 10.3389/fnagi.2023.1067268
|View full text |Cite
|
Sign up to set email alerts
|

Desflurane is risk factor for postoperative delirium in older patients’ independent from intraoperative burst suppression duration

Abstract: BackgroundPostoperative Delirium (POD) is the most frequent neurocognitive complication after general anesthesia in older patients. The development of POD is associated with prolonged periods of burst suppression activity in the intraoperative electroencephalogram (EEG). The risk to present burst suppression activity depends not only on the age of the patient but is also more frequent during propofol anesthesia as compared to inhalative anesthesia. The aim of our study is to determine, if the risk to develop P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…In our study cohort, anesthesia maintenance with volatile gases was a risk factor for the emergence of POD. This is in line with a previous retrospective study data analysis done by our group 37 and was also shown in a metaanalysis. 38 Hence, prospective studies should examine whether patients presenting the described EEG signatures after LOC would profit from a total intravenous anesthesia with propofol for anesthesia maintenance.…”
Section: Perioperative Medicinesupporting
confidence: 93%
“…In our study cohort, anesthesia maintenance with volatile gases was a risk factor for the emergence of POD. This is in line with a previous retrospective study data analysis done by our group 37 and was also shown in a metaanalysis. 38 Hence, prospective studies should examine whether patients presenting the described EEG signatures after LOC would profit from a total intravenous anesthesia with propofol for anesthesia maintenance.…”
Section: Perioperative Medicinesupporting
confidence: 93%
“…It is quite conceivable that the incidence of postoperative delirium in patients may be different when anesthetic agents other than sevoflurane are used. For example, a recent reanalysis of a study in older patients found that desflurane was associated with a higher risk of developing postoperative delirium as compared to propofol or sevoflurane, even though prolonged intraoperative burst suppression activity occurred with propofol [ 38 ]. In another study, older patients with elective lower extremity orthopedic surgery under spinal anesthesia were randomized to receive dexmedetomidine or propofol sedation.…”
Section: Discussionmentioning
confidence: 99%
“…After careful reading of the full-text articles, 32 studies were excluded ( Supplementary Table S3 ). Ultimately, this systematic review included 19 studies published between 2015 and 2023 (Soehle et al, 2015 ; Fritz et al, 2016 ; Hesse et al, 2019 ; Momeni et al, 2019 ; Pedemonte et al, 2020 ; Jung et al, 2021 ; Koch et al, 2021 , 2023 ; Lele et al, 2022 ; Li et al, 2022 ; Lutz et al, 2022 ; Röhr et al, 2022 ; Windmann et al, 2022 ; Baron Shahaf et al, 2023 ; Dragovic et al, 2023 ; Khalifa et al, 2023 ; Kinoshita et al, 2023 ; Reese et al, 2023 ; Ostertag et al, 2024 ). Additionally, 10 of these articles were included in the meta-analysis (Soehle et al, 2015 ; Hesse et al, 2019 ; Pedemonte et al, 2020 ; Jung et al, 2021 ; Koch et al, 2021 , 2023 ; Lele et al, 2022 ; Lutz et al, 2022 ; Röhr et al, 2022 ; Ostertag et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was noted that an increased incidence and duration of BSR and lower BIS values are also predictive of POD development. Nonetheless, several studies have not demonstrated an association between this parameter and POD (Koch et al, 2021 , 2023 ; Lele et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%